Effect of cooling rate on long-term recrystallized crystal of rice starch in the presence of flavor compounds. (30th May 2021) - Ma, Rongrong; Zhan, Jinling; Jiang, Zhongjie; Tian, Yaoqi
Highlights: Rapid cooling reduces the density and homogeneity of recrystallized crystals. Loose crystal and continuous nucleation mode contribute to flavor retention. Flavor compounds can be controlled in the initial stages of recrystallization. Results provide theoretical references for maintaining fragrance in instant rice. Abstract: This study evaluated the effect of cooling rate on starch recrystallization in the presence of 2, 3-butanedione and 2-acetyl-1-pyrroline, which could form B-type and V-type complexes with starch, respectively. Rapid cooling resulted in poor perfection and high heterogeneity of both B-type and V-type recrystallized crystal. For B-type crystal, rapid cooling changed nucleation mode from instantaneous (Avrami index n < 1) to continuous mechanism (1 ≤ n ≤ 2), and decreased recrystallization rate from 0.0502 to 0.0160 d − n, indicating the increased retention of starch on 2, 3-butanedione. V-type crystal was formed at initial stages of recrystallization, and inhibited the growth of B-type crystal. The loose crystalline obtained by rapid cooling is conducive to the retention of flavor compounds for B-type complexes (especially ≤14 days) and V-type complexes (especially ≤1 day). These results could provide guidance for maintaining fragrance of instant rice during long-term storage.